Productivity Improvement Through Work System Design Method For Better Man Power Utilization At Robot Welding Process - Chung, Kar Yee (2018)
In today’s marketplace, business has become more diversified and competitive in securing its market share. In order to sustain in business under the fierce competition, a company needs to eliminate the non-value added activities of the operation so that efficient and effective performance can be obtained. This study focuses on the improvement of productivity through effective utilization of manpower in the production line by using time study approach and MOST analysis. Three objectives have been set; (i) to identify the non-value added activities at the robot welding production line; (ii) to provide solution to reduce the non-value added activities at the welding production line; (iii) to increase the manpower utilization by 30%. Direct observation is conducted to determine the non-value added activities at the robot welding production line. Time study approach is applied to determine the actual cycle time of operator work content. MOST analysis was then presented to analyze the operation in a detail way which focused on the movement of object. Comparison between time study result and MOST analysis was conducted to investigate the operation. After that, a solution is provided to reduce the non-value added activities at the robot welding production line. Lastly, time study is carried out to validate the proposed solution. Results of the project show that; (i) non-value added activities at the robot welding production line are identified (i.e. list of the non-value added activities); (ii) a new work sequence layout has been proposed to reduce the operator waiting time; (iii) the manpower utilization has increased by 26.44% as well as the labor productivity has been improved by 66.67%. Thus, this study concludes that effective utilization of manpower can improve the labor productivity.